Correlation Stress, Body Mass Index and Physical Activities in Elderly with Hypertension - Noviana Dewi; Endang Widhiyastuti; Tri Harningsih; Sri Harini (GLOBAL HEALTH SCIENCE GROUP, 2022)
The physiological setbacks of the elderly include a decrease in the function of the cardiovascular system, which affects blood pressure in the elderly. One of the cardiovascular problems that often occurs in the elderly is hypertension. Hypertension is often associated with stress due to psychological problems from the elderly. In addition to stress, body mass index is another factor associated with hypertension. Overweight is one of the predisposing factors for the incidence of hypertension. In the elderly who are overweight, if followed by a low level of physical activity, will increase the risk of hypertension. This study aims to determine (1) the correlation between stress levels with hypertension in the elderly, (2) the correlation between BMI with hypertension in the elderly and (3)the correlation between physical activity with hypertension in the elderly. The population in this study was the participants of the Posyandu, an elderly rose in Kayuapak village. The sampling technique uses simple random sampling. Stress level variables are measured using DASS Test, BMI is measured by Digital Body Weight scales, physical activity is measured using a physical activity sheet and blood pressure is measured using a Spigmomanometer. This study uses correlational analysis techniques. The result is a relationship between stress levels and blood pressure in the elderly with a significance value of 0.039 <0.05 (p <0.05). There is a relationship between BMI and blood pressure in the elderly with a significance value of 0,000 <0.05 (p <0.05). There is a relationship between the level of physical activity with blood pressure in the elderly with a significance value of 0.011 <0.05 (p <0.05).